Analysis of the influence of the money supply and the rupiah exchange rate on stock returns of state-owned banks in the 2008-2010 period - Ramita Nurbaisya (Indonesia Auditing Research Journal, 2021)
Stock is one of the most popular capital market instruments among investors. Investors need information that can help them to make investment decisions, this information is collected in order to find out how much return they will receive as well as to prevent risks that may arise in the future. One of the information that investors need is the macroeconomic factors which could affect the stock price such as money supply, inflation, and the rupiah exchange rate. The objective of this study is to see the influence of macroeconomic variables (money supply and rupiah exchange rate) toward the stock returns of two state commercial banks, that is, Bank Mandiri and Bank Rakyat Indonesia, during the period of 2008-2010. This research uses multiple regression analysis models, t-tests.